Woman sits with a girl playing with legos - Unknown:::Creator::::::::::::
Photograph shows a woman sitting with a little girl who is playing with legos at a table. There are two other children at the table only partially visible in the photograph. They are probably at the YWCA's day care center. The picture of the jack-o-lantern face hanging in the background and a partial one on the table seems to indicate that it is close to Halloween.